A non-genomic action of 17 β-estradiol as the mechanism underlying the acute suppression of secretion of LH in primary cultures of ovine pituitary cells and in ovariectomized ewes - Arévalo, Jesús Alejandro Arreguín, author; Nett, Terry M., advisor; Handa, Robert, committee member; Anthony, Russell V., committee member; Niswender, Gordon, committee member; Clay, Colin M., committee member (Colorado State University. Libraries, 2004)
The first objective of this study was to determine the ability of 17 β-estradiol (E2) and conjugated forms of E2, (E2 conjugated to bovine serum albumin; E2 -BSA) and a novel synthesized conjugate (E2 conjugated to a 15 amino acid sequence; E2-PEP) to rapidly prevent the GnRH-induced secretion of luteinizing hormone (LH) and to determine the role of estradiol receptors (ERs) and ER subtypes in the mediation of the acute suppression of LH by E2 in primary cultures of ovine pituitary cells. In the first experiment, cells were incubated for 15 min with 0 to 100 nM of E2, E2-BSA or E2-PEP, plus 2 nM GnRH. In the second experiment, cells were treated with 100 nM of the following steroid hormones; progesterone (P4), testosterone (T), hydrocortisone (HC), 17 α-estradiol (17 α-E2), or the ERs antagonists tamoxifen (Tx), hydroxytamoxifen (HTx) or ICI 182,780 (ICI), with or without 1 nM of E2, E2-BSA or E2-PEP, plus 2 nM GnRH. In the last experiment, cells were incubated with 0 to 100 nM of the selective ERα estrogen agonist (PPT), or the selective ERβ estrogen agonist (DPN) plus 2 nM GnRH. Relative to GnRH treated cells, 0.1 to 100 nM of E2, E2-BSA or E2-PEP suppressed (P < 0.01) GnRH-induced secretion of LH. As expected incubation of pituitary cells with P4, T, HC or 17α-E2 did not affect LH secretion when given alone, nor impaired the inhibition of E2 on GnRH-induced secretion of LH (P > 0.1). Likewise, ER antagonists ICI, Tx or HTx did not affect (P > 0.1) secretion of LH when given alone, but they did prevent (P < 0.01) the inhibition of E2 and conjugated forms of E2 on GnRH-induced secretion of LH. Moreover, the selective ERα agonist but not the selective ERβ agonist decreased (P < 0.01) the GnRH-induced secretion of LH. The second objective was to determine how rapidly E2 was able to suppress LH secretion in ovariectomized (OVX) ewes and to evaluate the ability of conjugated forms of E2 to mimic the actions of E2 on LH and follicle stimulating hormone (FSH) secretion. Animals (n = 5 or 6 per group) were infused for 4 h with 50 μg E2 or equimolar concentration of E2-BSA or E2-PEP. LH and FSH were quantified from blood samples taken every 15 min from 4 h before to 5 h after the beginning of the infusion, and every h for the next 19 h. E2, E2-BSA, and E2-PEP each induced an acute suppression in frequency of pulses of LH (< 20 min; p < 0.01). However, E2, but not E2-BSA or E2-PEP, induced the characteristic pre-ovulatory like surge of LH (at 10 h after priming treatment), and a decreased in secretion of FSH (at 4 h after priming treatments). In conclusion, in ovine pituitary cells, E2 and conjugated forms of E2 prevented GnRH-induced release of LH in a steroid specific way. The inhibitory actions of E2, E2-BSA or E2-PEP in GnRH-induced release of LH secretion were equally prevented by antagonistic compounds of ER, which suggest that ERs mediate this action. Moreover, the use of selective ER agonists indicates that acute inhibition of GnRH-induced release of LH by E2 occurs via ERα. The acute inhibition of secretion of LH induced by E2 in OVX ewes is not compatible with the classic genomic mechanism by which steroid hormones modulate cellular function. An acute, nongenomic action as the mechanism underlying the sudden suppression in secretion of LH is supported by the fact that, conjugated forms of E2 mimicked only the acute suppression of secretion of LH, without inducing the putative genomic actions of E2 on secretion of LH or FSH. The presumed impermeability of conjugated forms of E2 suggests that the plasma membrane is involved in mediating the acute effect of E2. The ability of E2-BSA and E2-PEP to mimic only the acute action of E2 justifies their further characterization as a tool for the study of acute, nongenomic plasma membrane-mediated actions of E2.